Red Blood Cell Membrane-Camouflaged PLGA Nanoparticles Loaded With Basic Fibroblast Growth Factor for Attenuating Sepsis-Induced Cardiac Injury - Li, Xinze; Hong, Guangliang; Zhao, Guangju; Pei, Hui; Qu, Jie; Chun, Changju; Huang, Zhiwei; Lu, Zhongqiu (Frontiers in Pharmacology, 2022)
Cardiac injury is recognized as a major contributor to septic shock and a major component of the multiple organ dysfunction associated with sepsis. Emerging evidence show that regulation of the intramyocardial oxidative stress and inflammatory response have a promising prospect. Basic fibroblast growth factor (bFGF) exhibits anti-inflammatory and antioxidant properties. In this study, red blood cell membrane-camouflaged poly (lactide-co-glycolide) nanoparticles were synthesized to deliver bFGF (bFGF-RBC/NP) for sepsis-induced cardiac injury. The in vitro experiments revealed that bFGF-RBC/NP could protect cardiomyocytes from oxidative and inflammatory damage. In addition, the antioxidant and anti-inflammatory properties of bFGF-RBC/NP against cardiac injury were validated by data from an in vivo experiment. Collectively, our study used bFGF for the treatment of sepsis-induced cardiac injury and confirmed that bFGF-RBC/NP has therapeutic benefits in the treatment of myocardial dysfunction. This study provides a novel strategy for preventing and treating cardiac injury in sepsis.